2017
DOI: 10.1097/pec.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Computed Tomography Use for Evaluation of Head Injury in a Pediatric Emergency Department

Abstract: Physicians at our pediatric hospital ED varied in the use of CT for the evaluation of head-injured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
17
1
1
Order By: Relevance
“…This finding differs from several other studies where either no association was found between rate of injury and CTB use or imaging variation persisted even after accounting for injury prevalance . Physician background and training was not collected as part of this study but has been associated with differential scanning rates in other studies . Furthermore, while access to, and clinician comfort with, admission or observation in Australia and New Zealand as an alternative to immediate CTB may explain differences between our rates and those noted internationally, there was no consistent relationship between LOS ≥4 h and CTB rates across sites.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…This finding differs from several other studies where either no association was found between rate of injury and CTB use or imaging variation persisted even after accounting for injury prevalance . Physician background and training was not collected as part of this study but has been associated with differential scanning rates in other studies . Furthermore, while access to, and clinician comfort with, admission or observation in Australia and New Zealand as an alternative to immediate CTB may explain differences between our rates and those noted internationally, there was no consistent relationship between LOS ≥4 h and CTB rates across sites.…”
Section: Discussioncontrasting
confidence: 97%
“…In our cohort, this group had a lower rate of CTB use and a lower admission rate. Lower scan rates have been noted elsewhere, although this has not been universally reported . The lower scan rate in this group may be driven by concerns about the age related lifetime cancer risks with radiation exposure .…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations